Hallazgos: problemas y conceptos - Mejía Correa, María Paulina; Fernández Fuente, Sofía; Toro Ángel, Gloria Luz; Cortés Palomino, Marlon Yezid; Flórez Atehortúa, Sara (Revista Educación y Pedagogía, 2014)
*